(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
This study was conducted at leather industries of Hazaribagh, Dhaka to evaluate the tannery effluent quality. The samples of effluent were taken from seven leather industries and three places around the area of leather industries. The pH, Temperature, Colour, Odour, Electrical Conductivity (EC), Total Dissolved Solid (TDS), Cl-, NO2-, Alkalinity, Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), chromium ion (Cr3+), Suspended Solid (SS), phosphorous, sulphate (SO42-) were analyzed .The odour of the samples were more or less pungent. The colour of the samples was blackish blue, violet, brown, black etc. The values of pH, temperature, EC, alkalinity, DO, COD, BOD, Cl-, Cr3+, SS, TDS, NO2-, NO3-, phosphorous and SO42- of the samples were found in the range of 3.00-9.10, 26.4-30.27 oC , 897-1084 ?s/cm, 275-1410 mg/L, 0.34-4.10 mg/L, 510-2555 mg/L, 220-1010 mg/L, 820-1930 mg/L, 1.02- 20.32 mg/L, 1310-2010 mg/L, 2910-3740 mg/L, 0.74-3.15 mg/L, 6.31-23.49 mg/L, 7.45-9.35 mg/L and 125-510 mg/L respectively. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17324 Bangladesh J. Sci. Ind. Res. 48(3), 155-166, 2013